Ligularia pyrifolia var. dissecta (Asteraceae, Senecioneae), a remarkable new variety from southwestern Yunnan, China - Wang, Long; Zeng, You-Pai; Chen, Jun-Ren; Yang, Qin-Er (Phytotaxa, 2018)
Ligularia pyrifolia var. dissecta (Asteraceae, Senecioneae), a remarkable new variety from Wuliang Shan in Jingdong, southwestern Yunnan, China, is described and illustrated. It is most readily distinguishable from the type variety, var. pyrifolia, by having dissected (vs. undivided) leaves, a rare character in the genus Ligularia.